“Family Keepers” or “Career Seekers”: Understanding the Life Experiences and Educational Trajectories of the Young Chinese Restaurant Owners in the United States - Yuejia Wang (International Journal of Sociology of Education, 2023)
This qualitative research investigates how Chinese restaurant owners negotiate their education opportunities, family solidarity, and social identity during their migration for success in the United States. The researcher conducted in-depth interviews with nine Chinese restaurant owners in Western New York and identified two types of participants on the basis of their family backgrounds and educational attainments: the "family keepers" and the "career seekers". In short, "family keepers" tend to see ethnic business ownership as a way to sustain their families, while "career seekers" regard the ethnic business as a jumping-off point toward a new career. Incorporating the concept of transnational habitus from Bourdieusian scholars, this study argues that immigrants develop different transnational habitus within which they constantly reframe distinct mechanisms to evaluate their ethnic, family, and human capital for upward social mobility. By offering a comprehensive lens to understand immigrants’ human agency in coping with social and racial inequity, this study suggests one’s capital is dynamic and two-sided when transferring internationally. A certain type of capital denotes both advantages and disadvantages in immigrants’ transnational journey. It also raises the significance of with-group variance in understanding new immigrants’ upward social mobility.